PENETAPAN TARIF PEMERIKSAAN LABORATORIUM PATOLOGI KLINIK BERDASARKAN METODA JAROS ML - Maria I; Diah P; Tahono . (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
A hospital as an institution of public health assistance expected to extend comprehensive service and complex appropriate around public demand, capable of sophisticated laboratory examination with achievable cost. To be successful in the financial management of thelaboratory, we must be able to identify and categorize costs, understand the relationship between revenue and reimbursement, becomefamiliar with the budget process and use financial ratios and information to make sound decisions. Cost per test laboratory examinationsare needed to determine the real costs, cost information, and to appraise examination efficiency and budget. Laboratory costing per testbased on Jaros ML method demonstrates various ways to determine the cost of a test and how to establish its charge. The greater thedemand laboratory tests per month, the lower the cost per reportable result (CPRR) and the greater the efficiency of laboratory test.